Butanol production by Clostridium acetobutylicum ATCC 824 using electro-fermentation in culture medium supplemented with butyrate and neutral red - Guerrero, Karlo; Gallardo Marusich, Roberto Andres; Gonzalez, Ernesto; Veliz, Fabian; Conejeros, Raul; Gentina, Juan Carlos; Aroca, German (My University, 2022)
BACKGROUND Butanol is a versatile chemical that can be used as fuel, solvent or intermediate in chemical synthesis. Several strategies have been used to increase the availability of reducing power in Clostridium sp. with the aim of maximizing the production of butanol, the use of electron carriers being one of the most effective. Moreover, electrons from an external power source can be transferred to cells through electron carriers such neutral red, or directly reducing NAD(+). From a previous metabolic analysis, we hypothesized that adding butyrate to the culture medium and using an external electron source as a co-reducing agent, along with glucose-derived reducing power (electro-fermentation), would result in an increase in the specific butanol productivity. RESULTS Butyrate caused a decrease in the maximum concentration of butanol reached at the concentration used (6 g L-1). The supplementation of neutral red to the culture medium by itself and along with electro-fermentation were effective in stimulating the production of butanol. The mean specific rate of butanol production obtained for electro-fermentation in medium supplemented with butyrate and neutral red was 307% and 156% higher than that recorded using medium supplemented with butyrate, or butyrate and neutral red, respectively, this value being even 113% higher than that recorded for the non-supplemented medium. CONCLUSIONS The presence of butyrate and absence of neutral red in the electro-fermentation were detrimental for the microorganism. The electro-fermentation in medium supplemented with neutral red led to an increase in both volumetric and specific productivities of butanol. (c) 2021 Society of Chemical Industry (SCI).
Keywords: clostridium acetobutylicum; butanol; butyric acid; electro-fermentation; neutral red